Learning Self-Control * - Ali, S. Nageeb (Quarterly Journal of Economics, 2011)
This article examines how a decision maker who is only partially aware of his temptations learns about them over time. In facing temptations, individuals use their experience to forecast future self-control problems and choose the appropriate level of commitment. I demonstrate that rational learning can be perpetually partial and need not result in full sophistication. The main result of this article characterizes necessary and sufficient conditions for learning to converge to full sophistication. I apply this result to a consumption-savings environment in which a decision maker is tempted by present bias and establish a learning-theoretic justification for assuming sophistication in this setting. "An individual who finds himself continuously repudiating his past plans may learn to distrust his future behavior, and may do something about it." – Copyright 2011, Oxford University Press.